2015
DOI: 10.1016/j.dt.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment optimization for tensile properties of 8011 Al/15% SiCp metal matrix composite using response surface methodology

Abstract: In this study, a mathematical model was developed to optimize the heat treatment process for maximum tensile strength and ductility of aluminum (8011) silicon carbide particulate composites. The process parameters are solutionizing time, aging temperature, and aging time. The experiments were performed on an universal testing machine according to centre rotatable design matrix. A mathematical model was developed with the main and interactive effects of the parameters considered. The analysis of variance techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Unlike in many cast alloy and composite the dendrites with columnar structure are found to form in conventional casting technique. In present case using mechanical stirrerto create vortex and stirring molten metal, the dendrites are broken and equi-axed globular grains are formed in both LM26 alloy and its composites [14].…”
Section: Methodsmentioning
confidence: 87%
“…Unlike in many cast alloy and composite the dendrites with columnar structure are found to form in conventional casting technique. In present case using mechanical stirrerto create vortex and stirring molten metal, the dendrites are broken and equi-axed globular grains are formed in both LM26 alloy and its composites [14].…”
Section: Methodsmentioning
confidence: 87%
“…From the results, it was revealed that the tensile strengths of the heat treated composites are higher compared to un-heat treated composites. The improvement in ductility of MMCs can be attributed to the coupling effect of a numerous small hard ceramic particles due to growth restriction and also thermal modification at the time of heat treatment [26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metal cutting processes take advantage of RSM optimization [57,58]. In addition, RSM has entered materials sciences [59]. With regard to SP, prevention of Almen strip wastes and time during the detection of pre-shot peening conditions make the usability of statistical methods meaningful.…”
Section: Response Surface Methodologymentioning
confidence: 99%